2021
DOI: 10.1136/neurintsurg-2021-018175
|View full text |Cite
|
Sign up to set email alerts
|

Real-world outcomes associated with the use of the EmboTrap revascularization device for ischemic stroke in the United States

Abstract: BackgroundMechanical thrombectomy (MT) has become the standard of care for the treatment of acute ischemic stroke (AIS). The EmboTrap revascularization device (CERENOVUS, Johnson & Johnson Medical Devices, Irvine, California, USA) has an innovative, dual layer feature designed to facilitate thrombus retrieval.ObjectiveTo investigate the real-world clinical and economic outcomes among patients with AIS undergoing MT using the EmboTrap device in the United States (US).MethodsAdult patients (≥18 years) who un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…ARISE II found that 5.3% of trial patients experienced a sICH, while the rate in real-world studies ranged from 0.0% to 6.3% [ 30 , 33 , 43 , 63 ]. These studies were recently published in a single-arm review of EmboTrap treatment that corroborates our EmboTrap-specific findings: Bai et al [ 76 ] meta-analyzed the aforementioned studies as well as two publications that report EmboTrap in combination with aspiration catheters [ 77 , 78 ]. Bai et al corroborated the findings of MASTRO I, in that rates of successful mTICI 2b–3 (90%) and mFPR mTICI 2b/3 (43%) were slightly higher than our findings, while FPR mTICI 2c/3 (36%) and mRS 0–2 (53%) were slightly lower.…”
Section: Discussionsupporting
confidence: 84%
“…ARISE II found that 5.3% of trial patients experienced a sICH, while the rate in real-world studies ranged from 0.0% to 6.3% [ 30 , 33 , 43 , 63 ]. These studies were recently published in a single-arm review of EmboTrap treatment that corroborates our EmboTrap-specific findings: Bai et al [ 76 ] meta-analyzed the aforementioned studies as well as two publications that report EmboTrap in combination with aspiration catheters [ 77 , 78 ]. Bai et al corroborated the findings of MASTRO I, in that rates of successful mTICI 2b–3 (90%) and mFPR mTICI 2b/3 (43%) were slightly higher than our findings, while FPR mTICI 2c/3 (36%) and mRS 0–2 (53%) were slightly lower.…”
Section: Discussionsupporting
confidence: 84%
“…Third, distal embolism during retraction may be limited by a distal closed structure at the tip of the stent [ 20 21 22 ]. Fourth, the inner closed-cell stent might stabilize the engaged clot during retrieval [ 28 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…8 Several trials have demonstrated the clinical benefit and superior reperfusion efficacy of MT using stent-retriever thrombectomy devices over standard medical therapy in treating AIS-LVO. [4][5][6][7][8][9][10] In the guidelines from American Heart Association/American Stroke Association, MT using stent retrievers has been recommended. 5 The EmboTrap Thrombectomy Device was originally designed for more effectively trapping, retaining, and removing clots through its unique design of dual-layer and a distal capture zone.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 1230 patients were eligible for inclusion criteria. [8][9][10][11][12][19][20][21][22] Among the pooled studies, 6 studies and 1070 individuals used the EmboTrap II device only, and the remaining 3 studies and 160 individuals used the EmboTrap System only. The inclusion and exclusion criteria of patients in included studies are summarized in the Online Supplemental Data.…”
Section: Study Selection and Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation